2020
DOI: 10.1002/anie.202007745
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Speciation Determines Interfacial Chemistry: X‐ray‐Induced Lithium Fluoride Formation from Water‐in‐salt Electrolytes on Solid Surfaces

Abstract: Super-concentrated "water-in-salt" electrolytes recently spurred resurgent interest for high energy density aqueous lithium-ion batteries.T hermodynamic stabilization at high concentrations and kinetic barriers towards interfacial water electrolysis significantly expand the electrochemical stability window,facilitating high voltage aqueous cells.Herein we investigated LiTFSI/H 2 Oe lectrolyte interfacial decomposition pathways in the "water-in-salt" and "salt-in-water" regimes using synchrotron X-rays,w hich p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Suo et al demonstrated this principle with a 21 m LiTFSI water-in-salt electrolyte with a voltage window of 3 V and an upper voltage limit of 4.9 V versus Li/Li + and successfully applied it in full cells using Mo 6 S 8 and LiMn 2 O 4 as the anode and cathode, respectively. [167] There have been a variety of other "water-in-salt" studies using Li-salts dem-onstrating wider voltage windows from 2 V to >3 V. [169][170][171][172][173][174] Binary Li-salt mixtures, or "water-in-bisalt", have also been studied. A study by Ko et al achieved a voltage window of 4.85 V with an upper voltage window of 5.05 V using 22.2 m LiTFSI combined with 33.3 m LiPTFSI (which could be classified as a hydrate melt, given the lack of free water molecules), although the ionic conductivity was limited to 0.1 mS cm −1 .…”
Section: Highly Concentrated Aqueous Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Suo et al demonstrated this principle with a 21 m LiTFSI water-in-salt electrolyte with a voltage window of 3 V and an upper voltage limit of 4.9 V versus Li/Li + and successfully applied it in full cells using Mo 6 S 8 and LiMn 2 O 4 as the anode and cathode, respectively. [167] There have been a variety of other "water-in-salt" studies using Li-salts dem-onstrating wider voltage windows from 2 V to >3 V. [169][170][171][172][173][174] Binary Li-salt mixtures, or "water-in-bisalt", have also been studied. A study by Ko et al achieved a voltage window of 4.85 V with an upper voltage window of 5.05 V using 22.2 m LiTFSI combined with 33.3 m LiPTFSI (which could be classified as a hydrate melt, given the lack of free water molecules), although the ionic conductivity was limited to 0.1 mS cm −1 .…”
Section: Highly Concentrated Aqueous Electrolytesmentioning
confidence: 99%
“…Suo et al demonstrated this principle with a 21 m LiTFSI water‐in‐salt electrolyte with a voltage window of 3 V and an upper voltage limit of 4.9 V versus Li/Li + and successfully applied it in full cells using Mo 6 S 8 and LiMn 2 O 4 as the anode and cathode, respectively. [ 167 ] There have been a variety of other “water‐in‐salt” studies using Li‐salts demonstrating wider voltage windows from 2 V to >3 V. [ 169–174 ] Binary Li‐salt mixtures, or “water‐in‐bisalt”, have also been studied. A study by Ko et al.…”
Section: Liquid Electrolytes For Hv‐libsmentioning
confidence: 99%
“…[13,14] Furthermore, anions also strongly interact with the, typically alkali, cations at such high concentrations, facilitating the formation of anion-derived solid-electrolyte interphases (SEI), [1,2,[14][15][16] highly dependent on the actual nature of the anions. [17] The exact mechanistic details of this SEI formation, likely direct electrochemical reduction [1,2,15,18] or nucleophilic attack of hydroxide ions that form during initially extensive water reduction [19] , is actively debated in current literature, and a superposition of both mechanisms appears likely to occur in practice. In WiS electrolytes, the oxidative stability is particularly improved due to the accumulation of bulky anions (e.g., TFSI) on the positive electrode and subsequent formation of a water exclusion zone.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the concentration of water at the positive interface, which mainly contains TFSI − anions [6,8] . However, the main reason for the extended voltage window is the formation of a solid electrolyte interface (SEI) layer that mainly consists of LiF as a result of the electrochemical decomposition of the TFSI anion [9–11] . Although most of the studies of WiS electrolytes were performed using the LiTFSI salt, [12–16] the WiS concept was extended to other metallic ions such as potassium, [17] sodium, [18–20] and zinc‐based [21] electrolytes [22] …”
Section: Introductionmentioning
confidence: 99%